Thermodynamic analysis of strawberry drying process in a cyclone type dryer - Akpinar, E. Kavak (Natl Inst Science Communication-Niscair, 2007)
In this paper, thermodynamic analysis of the thin layer drying process of strawberry are investigated. Drying experiments were conducted at inlet drying air temperatures of: 60, 75 and 85 degrees C and at drying air velocities of 0.5, 1 and 1.5 m s(-1) in a cyclone type dryer. Using the First Law of Thermodynamics, energy analysis was carried to estimate the ratios of energy utilization. However, exergy analysis was accomplished to determine type and magnitude of exergy losses during the drying process by applying the Second Law of Thermodynamics. Strawberry samples were sufficiently dried between 60-85 degrees C at 0.5, 1 and 1.5 m s(-1) or drying air velocity during 12000-33600 sec despite the exergy losses of 0-0.715 kJ s(-1).
Keywords: drying; strawberry; thermodynamic analyses